2016
DOI: 10.1017/s1047951116001177
|View full text |Cite
|
Sign up to set email alerts
|

eHealth literacy and preferences for eHealth resources in parents of children with complex CHD

Abstract: A total of 132 parents (83 mothers, 49 fathers) completed the survey (response rate: 50%). Mothers (96%) were more likely to access eHealth resources than fathers (83%, χ2=6.74, p=0.009). Despite high eHealth resource use, eHealth literacy was relatively low, with results demonstrating considerable and widespread gaps in awareness of, access to, and communication about eHealth resources. Over 50% of parents reported that decisions regarding their child's healthcare were influenced, to some extent, by web-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 35 publications
1
50
1
2
Order By: Relevance
“…The papers were sorted into 3 groups based on the focus of the paper ( Table 1 ). A total of 13 of the studies focused on OHIS related to a specific disease or disease cluster, including asthma [ 34 ], attention-deficit/hyperactivity disorder [ 35 ], brachial plexus birth palsies [ 36 ], congenital heart disease [ 33 , 37 , 38 ], diabetes [ 39 ], hearing loss [ 40 ], hydrocephalus [ 41 ], scoliosis [ 42 ], skin disorders [ 43 ], and rare diseases [ 44 , 45 ]. An additional 13 studies addressed specific circumstances, mainly prior to a surgical procedure [ 46 - 51 ], after childbirth [ 52 ], 24 hours before an emergency department visit [ 53 ], during stay in a neonatal intensive care unit [ 54 ], in a pediatric outpatient clinic [ 55 , 56 ], in palliative care [ 57 ], and regarding attitudes towards human papillomavirus vaccination [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The papers were sorted into 3 groups based on the focus of the paper ( Table 1 ). A total of 13 of the studies focused on OHIS related to a specific disease or disease cluster, including asthma [ 34 ], attention-deficit/hyperactivity disorder [ 35 ], brachial plexus birth palsies [ 36 ], congenital heart disease [ 33 , 37 , 38 ], diabetes [ 39 ], hearing loss [ 40 ], hydrocephalus [ 41 ], scoliosis [ 42 ], skin disorders [ 43 ], and rare diseases [ 44 , 45 ]. An additional 13 studies addressed specific circumstances, mainly prior to a surgical procedure [ 46 - 51 ], after childbirth [ 52 ], 24 hours before an emergency department visit [ 53 ], during stay in a neonatal intensive care unit [ 54 ], in a pediatric outpatient clinic [ 55 , 56 ], in palliative care [ 57 ], and regarding attitudes towards human papillomavirus vaccination [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The samples consisted of highly educated parents, with more than 50% [ 33 , 34 , 36 , 41 , 44 , 48 , 54 ] and up to more than 75% of parents holding academic degrees [ 52 , 58 , 63 ], but 14 studies did not report any educational levels. The proportion of persons with only primary education varied between 0% [ 52 ] and 21.9% [ 57 ] among the studies that reported on education levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting the high Internet usage for health‐related information in the current era , most parents did access web‐based information on CAKUT. However, there were concerns about the quality of eHealth information.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research identify interventions which focus on striving to change families' illness perceptions and coping mechanisms, as most effective in reducing parental stress [ 21 ]. Future research could explore the efficacy of newer methods using social media or e-health resources [ 22 , 23 ]. Given that parenting stress has also been linked to family resources [ 7 ], these findings highlight the important role which community support organizations could play in providing social and financial support to these families.…”
Section: Discussionmentioning
confidence: 99%